Work-life balance among sport scientists and coaches: Do as I say, not as I do - Sandbakk, Ø (International Journal of Sports Physiology and Performance, 2023)
Elite athletes continuously fine-tune their training quality, as well as the balance between training load and recovery, to optimize training adaptations and realize their long-term potential. Within this context, Haugen et al1 categorized training quality in 2 interconnected dimensions: quality of the holistic training process and quality of the execution of daily training sessions. Coaches teach athletes to employ various methods to improve these 2 dimensions of training quality. Already at a young age, athletes define SMART goals (ie, Specific, Measurable, Attainable, Relevant, and Timebound); perform subsequent gap analyses to reach those goals; perform detailed planning on macro, meso, and micro levels; write training logs; and regularly evaluate whether their development is going in the right direction. This process is usually performed in close collaboration between the athlete and a coach or mentor. In daily training, athletes learn that each session should have clear intentions that are followed by well-defined procedures for preparation, execution, and debriefing. In addition, the continuity required to optimize athletes` long-term development requires a 24-hour holistic approach in which sleep, nutrition, mental and physical well-being, and a sustained work-life balance are important factors.